An Architectural Battery Designed by Substituting Lithium with Second Main Group Metals (Be, Mg, Ca/Cathode) and Hybrid Oxide of Fourth Group Ones (Si, Ge, Sn/Anode) Nanomaterials Towards H2 Adsorption: A Computational Study - Mollaamin, Fatemeh; Monajjemi, Majid (MDPI AG, 2025)
Germanium/tin-containing silicon oxide [SiO–(GeO/SnO)] nanoclusters have been designed with different Si/Ge/Sn particles and characterized as electrodes for magnesium-ion batteries (MIBs) due to forming MgBe [SiO–GeO], MgBe [SiO–SnO], MgCa [SiO–GeO], and MgCa [SiO–SnO] complexes. In this work, alkaline earth metals of magnesium (Mg), beryllium (Be), and calcium (Ca) have been studied in hybrid Mg-, Be-, and Ca-ion batteries. An expanded investigation on H capture by MgBe [SiO–(GeO/SnO)] or MgCa [SiO–(GeO/SnO)] complexes was probed using computational approaches due to density state analysis of charge density differences (CDD), total density of states (TDOS), and electron localization function (ELF) for hydrogenated hybrid clusters of MgBe [SiO–GeO], MgBe [SiO–SnO], MgCa [SiO–GeO], and MgCa [SiO–SnO]. Replacing Si by Ge/Sn content can increase battery capacity through MgBe [SiO–GeO], MgBe [SiO–SnO], MgCa [SiO–GeO], and MgCa [SiO–SnO] nanoclusters for hydrogen adsorption processes and could improve the rate performances by enhancing electrical conductivity. A small portion of Mg, Be, or Ca entering the Si–Ge or Si–Sn layer to replace the alkaline earth metal sites could improve the structural stability of the electrode material at high multiplicity, thereby improving the capacity retention rate. In fact, the MgBe [SiO–GeO] remarks a small enhancement in charge transfer before and after hydrogen adsorption, confirming the good structural stability. In addition, [SiO–(GeO/SnO)] anode material could augment the capacity owing to higher surface capacitive impacts.
Keywords: Chemistry; hydrogen adsorption; energy storage; density of states; QD1-999; Article; alkaline earth metal-ion battery